(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
This article provides information about the importance of state policy in ensuring inter-ethnic harmony and religious tolerance in Uzbekistan. Also, the measures implemented in our country for religious tolerance and inter-ethnic harmony are reflected in the article